Case report: false positive elevated serum‐galactomannan levels after autologous hematopoietic stem cell transplantation caused by oral nutritional supplements. Issue 5 (12th April 2016) - Rachow, Tobias; Dornaus, Sebastian; Sayer, Herbert G.; Hermann, Beate; Hochhaus, Andreas; von Lilienfeld‐Toal, Marie
Key Clinical Message: Positive galactomannan tests in patients who underwent chemotherapy without any clinical signs of a fungal infection should lead the clinician to consideration of a false‐positive test result. Oral nutritional supplements may be a cause, especially in the case of concomitant disturbance of the gastrointestinal mucosal barrier because of mucositis. Abstract : Positive galactomannan tests in patients who underwent chemotherapy without any clinical signs of a fungal infection should lead the clinician to consideration of a false‐positive test result. Oral nutritional supplements may be a cause, especially in the case of concomitant disturbance of the gastrointestinal mucosal barrier because of mucositis.